Functional and quality of life assessment of patients with ankle ulcers subjected to complete Achilles tendon resection - Pires, Wrgelles Godinho Bordone; Maia, Philipe Eduardo Carvalho; Carvalho, Felipe Daniel Vasconcelos de; Castilho, Rodrigo Simões; Lopes, Fernando Araújo Silva; Pinto, Roberto Zambelli de Almeida (Scientific Journal of the Foot & Ankle, 2019)
Objective: To assess the quality of life and functional status of patients subjected to debridement of ulcers in the posterior ankle who required complete Achilles tendon resection without any type of reconstruction or tendon transfer. Method: This is a case series of 5 (mostly diabetic) patients who underwent complete Achilles tendon resection due to an ulcer in the posterior ankle region. Preservation of the Achilles tendon was prevented due to tendon exposure, extensive degeneration and the need for infection control. Patients answered the Brazilian Portuguese version of the Achilles Tendon Total Rupture Score (ATRS-BR) questionnaire and the 36-item Short-Form Health Survey (SF-36) during the postoperative period, and follow-up varied between 6 and 24 months. The ATRS-BR ranges from 0 to 100, and higher scores indicate fewer symptoms and limitations. The SF-36 consists of 36 questions comprising 8 domains, which are independently assessed and given a score of up to 100 points, with higher scores indicating better health status. Results: The mean age of patients was 70 years. The mean score on the SF-36 physical functioning domain was 70 (50-95) points. The mean value of the ATRS-BR was 54.6 (31-88) points; however, the patients had few complaints about their functional status. Conclusion: Non-reconstruction of the Achilles tendon in predominantly diabetic elderly patients with posterior ankle ulcers presents encouraging functional outcomes. This study suggests that complete Achilles tendon resection is a viable option for ulcer treatment in this population. Level of Evidence IV; Therapeutic Studies; Cases Series.